Search for flavor-changing neutral currents in top-quark decays t →zq in pp collisions at s =8TeV - Chatrchyan, S. (2014)
A search for flavor-changing neutral currents in top-quark decays t→Zq is performed in events produced from the decay chain tt̄→Zq+Wb, where both vector bosons decay leptonically, producing a final state with three leptons (electrons or muons). A data set collected with the CMS detector at the LHC is used, corresponding to an integrated luminosity of 19.7fb-1 of proton-proton collisions at a center-of-mass energy of 8 TeV. No excess is seen in the observed number of events relative to the standard model prediction; thus, no evidence for flavor-changing neutral currents in top-quark decays is found. A combination with a previous search at 7 TeV excludes a t→Zq branching fraction greater than 0.05% at the 95% confidence level. © 2014 CERN, for the CMS Collaboration.